PENGEMBANGAN ASESMEN INTERAKTIF BERBANTUAN LIVEWORKSHEETS DALAM MATA PELAJARANINFORMATIKA KELAS IX - Nurul Syahira; Novrianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the continued dominance of paper-based assessment at SMP Negeri 1 Lubuk Alung, where 61% of students used conventional tests, 64% did not receive immediate feedback, and 60% were unsatisfied with existing assessments. This study aimed to produce a valid and practical interactive assessment assisted by Liveworksheets in Informatics for Grade IX. The research employed the Research and Development (R&D) method using the 4-D model (Define, Design, Development, Disseminate). The product consisted of 15 interactive questions in five formats: multiple choice, drag and drop, matching, word search, and fill in the blank on Computer Networks and Internet material. Validation was conducted by assessment question and media experts, while practicality testing involved a teacher and 25 students of class IX-7 at SMP Negeri 1 Lubuk Alung. Validation results showed an overall average of 94.7% (very valid), teacher practicality reached 92.5%, and student practicality 96% (very practical). Thus, the developed Liveworksheets-assisted interactive assessment is valid and practical for use in Informatics learning evaluation at junior high school.Keywords: interactive assessment, liveworksheets, informatics, 4-D model, validity, practicality